Generation of mesoporous n-p-n (ZnO–CuO–CeO2) heterojunction for highly efficient photodegradation of micro-organic pollutants. Issue 3 (1st February 2023) - Aadil, Muhammad; Kousar, Tehmina; Hussain, Mehtab; Somaily, H.H.; Abdulla, Aliaa Kareem; Muhammad, Eman Ramzy; A.Al-Abbad, Eman; Salam, Mohamed Abdel; M.Albukhari, Soha; Baamer, Doaa F.; Ansari, Mohd Zahid
Abstract: In this research, a mesoporous rod-shaped ZnO/CuO/CeO2 n-p-n heterojunction has been designed via a two-step co-precipitation technique for photocatalytic applications. Characterization by powder X-ray diffraction (PXRD), fourier transform infrared spectroscopy (FTIR), UV–Vis, and Scanning Electron Microscopy (SEM) techniques confirmed the formation of mesoporous rod-shaped ZnO/CuO/CeO2 n-p-n heterojunction having preferred interface developing between the ZnO, CuO, and CeO2 phases, thus extended the light-absorption window up to 800 nm. Under sunlight, the ability of a mesoporous ZnO/CuO/CeO2 n-p-n heterojunction to act as a photocatalyst was tested with methyl orange (MO) and crystal violet (CV) as target molecules. We found the degradation efficiencies of CV and MO dyes on mesoporous ZnO/CuO/CeO2 to be 96% and 88%, respectively, after 90 min of sunlight irradiation. The estimated rate constants (k, min −1 ) for deterioration of CV and MO under sunlight over ZnO/CuO/CeO2 composite were 0.039 and 0.022 min −1, respectively. We endorsed the greater photo-response, the well-aligned band-structure, and practical usage of the photo-induced carriers of the mesoporous photocatalyst to be the leading causes for the outstanding photocatalytic properties of ZnO/CuO/CeO2 n-p-n heterojunction. The ultimate oxidizing species that destroyed dyes were O2 ‾ and ·OH over ZnO/CuO/CeO2 photocatalyst under sunlight illumination. Besides, the recycling tests confirmed the high photostability of the ZnO/CuO/CeO2 photocatalyst. Hopefully, the mesoporous rod-shaped architecture of the n-p-n heterojunction with anticipated interface manufacturing will assist the photocatalyst strategy with better photocatalytic action under sunlight irradiation. Graphical abstract: Image 1